Effective current drive in the pedestal region of high-confinement tokamak plasma using electron cyclotron waves. (1st September 2022) - Li, C.Y.; Zheng, P.W.; Jiang, X.C.; Lu, L.F.; Yin, L.; He, L.H.; Q.H., Huang; Zhong, Y.J.; Gong, X.Y.
Abstract: Large-amplitude edge-localized modes (ELMs) are a major concern in the development of tokamak fusion energy. According to the peeling–ballooning theoretical model, effective current drive in the pedestal region of high-confinement (H-mode) tokamak plasmas can alter the current profile in this region and hence affect ELM instabilities. Using ray-tracing and Fokker–Planck quasilinear codes, effective and localized current drive by electron cyclotron (EC) waves in the H-mode pedestal region is studied in this paper. Numerical investigations are performed under present-day medium-sized tokamaks with an aspect ratio ( A = R / a ) covering a typical range of [2.7, 4.0]. Localized non-inductive current can be generated effectively by the Ohkawa mechanism of EC waves in the low-electron collisionality H-mode pedestal region. The Ohkawa mechanism-dominated current drive (OKCD) is much more effective than traditional electron cyclotron current drive (ECCD), which is the Fisch–Boozer mechanism-dominated one. Under 1–2 MW EC power, the current density of both co-OKCD and counter-OKCD has the same magnitude as edge bootstrap current density, which is calculated using the Sauter model. However, edge ECCD is much smaller than the bootstrap current. Consequently, the use of edge ECCD to control ELM failed in experiments, and only the EC heating can affect ELM behavior. Simulations on OKCD are performed in the H-mode pedestal region of realistic DIII-D tokamak plasma, and the results also support the above conclusions. The dependence of effective edge OKCD on the ratio of magnetic field and EC frequency is also found in tokamaks with a typical aspect ratio range. This work opens up a new possible field for active control of ELMs (triggering or suppressing an ELM) by edge current drive in present-day medium-sized tokamaks.